Community development plan: Rural livestock, agriculture and livelihood in Indonesia - Guntoro, Budi (Journal for Geography, 2010)
This study aimed to determine the bio-physical and socio-economic characteristics of the community, to determine the problems encountered by the community with emphasis on livestock, agriculture and livelihood and to recommend appropriate plans of action in addressing these problems. Field observation and interviews with key informants were conducted.  The data gathered served as basis in the preparation of a Community Develop-ment Plan for Lopati Village, Yogyakarta Province, Indonesia, which was the ultimate goal of the activity. In addition, this data provided guidelines in plan implementation as well as serving as a basis for determining the different changes or accomplishments to be made.  Eight key informants were involved in the interview. The results showed that there are many problems faced by the community, including low income, lack of capital and credit sources, low prices of products and business management.  Several plans of action that were made and proposed included strengthening of the existing farmers’ multipurpose cooperative, conversion of the farmers and women’s association into a cooperative, introduction and implementation of swine dispersal project, intensification of cattle, goat and duck raising, home industries, introduction of purely self-help projects, training workshops for farmers, youth and women, competitive farm gate prices for the community’s products, payment of previous loans, encouragement/reactivation of other banks to participate in a credit program, and general assembly meeting/monitoring and evaluation of projects/program.